PENGARUH PENGGUNAAN MEDIA TIGA DIMENSI JARING-JARING KUBUS TERHADAP KEMAMPUAN VISUALISASI SPASIAL PESERTA DIDIK KELAS VI PADA MATERI GEOMETRI DI SDN PAYAMAN - Ika Fitriyah Tyastuti; Refni Adesia Pradiarti; Sabar; Mila Erdiana (STKIP Subang, 2025)
This study aims to determine the effect of using three-dimensional media in the form of cube nets on the spatial visualization abilities of sixth-grade students in geometry at SDN Payaman. This study uses a quantitative approach with a quasi-experimental design involving two groups of students, namely the group that received learning using three-dimensional cube net media and the group that received conventional learning. Data collection was conducted through spatial visualization ability tests administered before and after the treatment. The research procedure included the stages of planning, preparing learning tools, implementing learning, collecting data, and processing data systematically. Data analysis used descriptive statistical techniques to describe the data and inferential techniques to compare the improvement in ability between the two groups. The results showed that the use of three-dimensional cube net media resulted in a higher increase in spatial visualization skills compared to conventional learning. Students demonstrated a better understanding in recognizing shapes, mentally rotating objects, and connecting two-dimensional and three-dimensional representations. The conclusion of this study states that three-dimensional cube net media has a positive effect on students' spatial visualization skills and can be used as an alternative learning medium for geometry material.